Perkembangan dan struktur organisasi Assemblies of God / Tan Swee Lin - Tan , Swee Lin (1984)
This study conducted on the Assemblies of God has been arranged into 4 main chapters. Chapter 1 deals with how the A.O.G. began . Briefly, the church started with a group of people who had believed and experienced the outpouring of the Divine Spirit accompanied by the phenomenon of speaking in tongues. This feature drew the believers together to form a new movement called the Pentecostal movement, the end-result of which was the Assemblies of God. Chapter 2 outlines the early missionary programmes in the A.O.G., gives a glance-over of these programmes, how they are conducted, by whom and for what reason. It also explains why the Pentecostal movement flourished at such a rapid pace. Chapter 3 brings the A.O.G. closer to home and observes its growth and expansion in Malaysia, giving an idea of how the A.O.G. took root in this country and traces its gradual influence on the people. Chapter 4 comes forth with a study of the Emmanuel A.O.G., situated in Ipoh. It gives as detailed as possible an account of how an A.O.G. church works, giving particular attention to the programmes. Chapter 5 rounds up the project with an attempt to evaluate and understand the position of the A.O.G. in the light of the world.